Akibat Hukum Cacat Kehendak dalam Perjanjian Jual Beli Melalui Pinjaman Online Pada E-Commerce - Ayusari Chandraningtyas; Sulastri (Fakultas Hukum, Universitas Warmadewa, 2024)
Technological advancements have transformed the lifestyle of society in various fields, including the economy, education, social aspects, and others. This is evident in the increasing number of internet users, one of which is e-commerce. Transactions conducted on e-commerce platforms are considered valid when there is an electronic contract or other form of agreement indicating the consent of the parties involved. Typically, this electronic contract is represented by the terms and conditions of the e-commerce platform. However, what if the contract contains elements of defective consent, such as fraud, misrepresentation, or coercion? In several prior studies found by the researcher, there has been no discussion of the elements of defective consent in online purchase agreements involving online loans in e-commerce. This research contributes to understanding the legal consequences related to defective consent in online purchase agreements, provides guidance for avoiding potentially problematic transactions, and highlights the need for better supervision of online purchase transactions involving online loans in e-commerce. This study employs a juridical-normative method, and the approach used is the statutory approach and the case approach. The research delves into the validity of purchase agreements involving online loans in e-commerce and their legal implications concerning defective consent. The research discusses the validity criteria of agreements based on the Civil Code and the Electronic Information and Transactions (ITE) Law. In the context of purchase transactions, the agreement's validity is recognized if both subjective and objective criteria are met. However, defective consent, such as misrepresentation and fraud, can affect the validity of the agreement, which can be annulled if the subjective criteria are not met.